Memulihkan Penerimaan Pajak Pasca Pandemi Covid-19 - Charoline Cheisviyanny (Politeknik Keuangan Negara STAN, 2020)
This research aims to offer some solutions to recover tax revenue pasca Covid-19 pandemy. This research is an explorative research with a quantitative approach. The data used was the annual reports of companies listed in BEI. This research used purposive sampling method to select samples and got 219 samples for 2017 and 217 samples for 2018. The proposed suggestions in recovering tax revenue are: (1) optimalization of withholding tax mechanism, (2) final tax imposition for non SMEs, and (3) reduction of tax audit and tax dispute. These suggestions need further dan depth review before implemented.